STUDENT WORKSHEET WITH FLIPPED CLASSROOM APPROACH ON DYNAMIC FLUIDS MATERIAL: LEMBAR KERJA PESERTA DIDIK (LKPD) DENGAN PENDEKATAN FLIPPED CLASSROOM PADA MATERI FLUIDA DINAMIS - Elsa Oktaviani; Hadi Nasbey; Upik Rahma Fitri (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2025)
This study aims to develop a worksheet with a Flipped Classroom approach so that it can be used as a feasible learning support for students on Fluid Dynamics material. The research method used is research and development (Research and Development) with the ADDIE model (Analyze, Design, Develop, Implement, and Evaluate). The steps in this research are conducting a needs analysis, making product designs, conducting product validation tests to experts, conducting limited product trials to students, and evaluating. Needs analysis has been carried out in several high schools in Jabodetabek, precisely in class XI MIPA students who have studied Fluid Dynamics material. From the results obtained that 81.4% of 43 respondents stated that Fluid Dynamics material was difficult material in physics subjects and some of them also had difficulty doing practicum on dynamic fluid material. Therefore, a worksheet with a Flipped Classroom approach on Fluid Dynamics material was developed which can be used as a feasible learning support.